Edukasi Publik melalui Refleksi Budaya Visual Beksan Trunajaya Keraton Yogyakarta dalam Perspektif Semio-Edukatif - Mela Dina Arumsari; Kuswarsantyo Kuswarsantyo; Moh. Rusnoto Susanto (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The classical ballet Beksan Trunajaya was initiated by Sri Sultan Hamengkubuwana I which means that Taruna means young, and Jaya means winning) using lawung weapons (in the form of spears) depicted through warfare. The spirit of Beksan Tunajaya is intended as an effort to foster a patriotic spirit in defending the homeland as inherited by Sultan Agung when expelling the Dutch invaders. This research aims to (1) describe the process of public education through the reflection of art values and visual culture of Beksan Trunajaya of Yogyakarta palace in semio-educative perspective, (2) describe the cultural dimension of public education as a reflection of visual culture of Beksan Trunajaya of Yogyakarta palace in semio-educative perspective. The type of qualitative research with Barthes' semiotic approach used with a pedagogical perspective, the semio-educative approach results in the merging of semiotic theory and the basis of educational theory. In this thesis research activity explores the sign system in the visual aspects of the classical dance performance Beksan Trunajaya, namely in the visual aspects of makeup and clothing and other cultural expressions as a substantial philosophical reflection of life. Through the process of extracting visual sign relationships and extracting denotative and connotative meanings and myths to reflect public education values. The research results that can be stated are: (1) presenting crusial the results of a critical review of the relationship between culture and public education through visual cultural expressions presented through Beksan Trunajaya in a semio-educative perspective. (2) Expansion of the results of the analysis of the cultural dimensions of public education as a reflection of the visual culture of Beksan Trunajaya of the Yogyakarta Palace in a semio-educative perspective.